Thinned continental crust intruded by volcanics beneath the northern Bay of Bengal. (November 2016) - Sibuet, Jean-Claude; Klingelhoefer, Frauke; Huang, Yuan-Ping; Yeh, Yi-Ching; Rangin, Claude; Lee, Chao-Shing; Hsu, Shu-Kun
Abstract: Since the early Cretaceous, the Bay of Bengal was formed during rifting between India and Antarctica and then by subsequent seafloor spreading. The nature of the crust underlying the Bay of Bengal is oceanic south of 15°N, but remains unknown (thinned continental crust, serpentinized mantle or oceanic crust) north of this limit. In order to better define the nature of the crust in the northern Bay of Bengal, three wide-angle reflection seismic and refraction profiles were acquired during the multichannel seismic reflection Bengal cruise. Nine ocean-bottom seismometers were deployed alternatively on three profiles. A seismic source consisting of 64 air guns with a volume of 6180 in 3 was used simultaneously with a 10.05-km long streamer to acquire both seismic reflection and refraction data. Tomographic and forward modelings of the three refraction profiles reveal a 20-km thick crust north of the Bengal delta front beneath a minimum of 13 km thick sedimentary cover. The crust thins to about 10 km immediately south of the EW trending delta front and the thickness of sediments reaches a minimum of 7 km. Crustal velocities and velocity gradients are consistent with a continental origin of the crust in this area. At the base of the crust, high seismic velocities (>7.2 km/s) are interpreted as magmatic underplating. Wide-angle seismic reflection and refraction data cannot resolve the nature of the upper 4–5 km of crust (oceanic crust, exhumed mantle or thinned continental crust). But coincident seismic reflection profiles show the emplacement of a volcanic intrusion, sills and some seaward dipping reflectors (SDRs) located close to the northern prolongation of the Ninety East ridge before 70 Ma (Maastrichtian). However, most of the fan-shaped reflectors identified in the northern Bay of Bengal are synrift features. We conclude that the crust in the northern Bay of Bengal is thinned continental crust intruded by volcanic products with the presence of a minor amount of underplating material at its base. Such a crustal structure probably extends from the northern Bay of Bengal (19°N) to the Shillong Plateau (25°N). These new findings are critical for the oil and gas exploration presently very active in the northern Bay of Bengal area. Highlights: Refraction velocity models show a sedimentary cover of 13 km minimum beneath the shelf and 7 km minimum beneath the deep ocean. The crust is thinned continental crust, 10–20 km thick. The thinned continental crust is intruded by volcanics, sills and SDRs. Seismic velocities of 7.4 km/s found at the base of the crust is interpreted as magmatic underplating. The thinned continental crust extends from 19°N (northern Bay of Bengal) to 25°N (Shillong Plateau).